Dying While Living: Exploring the practice of dying daily through meditation (Journal of Advances and Scholarly Researches in Allied Education, 2015)
To die daily means to practice the withdrawal of the consciousness tothe eye center every day. That is why meditation is known as dying daily. Inmedication, we withdraw over consciousness to the eye center in the same waythat we all die when death comes. First, the feet become numb, then the legs,and slowly the whole body becomes numb. When the soul withdraws from the nineapertures and comes to eye center, it leaves the body. In the ‘The Book ofMirdad, Mirdad said, die to live. We must withdraw to the eye center, and thenwe will live forever. Medication is nothing but a preparation to leave thebody. That is the real purpose of Meditation. In this paper, I want to expressmy view that we die daily in meditation, but not the real death. It’s just apractice how to die every day and that is meditation.